Molecular origins of wettability of hydrophobic poly(vinylidene fluoride) microporous membranes on poly(vinyl alcohol) adsorption: Surface and interface analysis by XPS - Gholap, S. G.; Badiger, Manohar V.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry B, 2005)
irreversible adsorption of poly(vinyl alcohol) (PVA) on hydrophobic, porous poly(vinylidene fluoride) (PVDF) membranes was carried out using aqueous PVA solution. Water permeation was observed in PVDF microporous membranes after PVA adsorption, and maximum permeability was obtained after treatment with 4% PVA solution. Water permeability increased linearly with increasing PVA concentration up to 4%, and then a marginal decrease with a further increase in PVA concentration occurred. PVA adsorbed PVDF membranes were subjected to intense physicochemical analysis, especially with XPS. XPS results display the presence of an interface between PVA and PVDF, and the binding energy (BE) of the interface is low for the PVDF membranes treated with 4% PVA. Carbon from CF2-groups and F 1s core level clearly showed a decrease in its content on the surface after PVA adsorption and showed a minimum fluorine content at 4% PVA. F Is BE shifts by 0.5 eV upon PVA adsorption and is independent of PVA concentration. EDAX analysis indicates that the bulk oxygen content remains within 4.5 +/- 0.6% and is independent of the PVA concentration. Nonetheless, a large amount of surface atom percentage of oxygen (20 +/- 4%) from 0 Is core level shows an increase in PVA content on the surface of PVDF, and it is restricted mostly to the surface. The 4% PVA treated PVDF membrane clearly shows a broadening of O 1s core level to lower BE and indicates the interaction between PVDF and PVA which is significantly different compared to any other compositions. A new valence band feature at low BE, which is nonexistent on PVDF, develops after PVA adsorption. This indicates that the shift in the nature of the highest occupied molecular orbital (HOMO) derived mostly from oxygen; simultaneously, a suppression in the PVDF derived band indicates the change in nature of the PVA adsorbed surfaces from hydrophobic to hydrophilic. The above observations also suggest an irreversible electronic interaction between PVA and PVDF, possibly through charge transfer.

Morphology and chain dynamics during collapse transition of PNIPAM gels studied by combined imaging, relaxometry and Xe-129 spectroscopy techniques - Kariyo, Sobiroh; Kuppers, Markus; Badiger, Manohar V.; Prabhakar, A.; Jagadeesh, Bharatam; Stapf, S.; Blumich, B. (Magnetic Resonance Imaging, 2005)
The temperature-induced shape transition of poly(N-isopropylacrylamide) gels of different cross-link densities was investigated by a combination of NMR techniques allowing the characterization of both the macroscopic collapse as well as the changes on a molecular scale related to the expulsion of water from the gel network. The proton-containing gel phase was visualized by swelling in heavy water, and the volume change was monitored by proton imaging for cross-link densities between 0.5 % and 2.5 %. Above the transition temperature of 35 degrees C, gel collapse led to a volume change of up to a factor of 17 for the gel of smallest cross-link density. Two spectral lines of Xe-129 are found in the gel state and are assigned to the hydrophobic and hydrophilic parts of the network. In the collapsed state, the hydrophobic peak shows a strong shift while the hydrophilic peak disappears. A considerable shortening of both T-1 and T-2 of the gel protons upon collapse was found at a field of 4.7 T. At lower fields, the effect becomes more pronounced and qualitatively different dispersion behaviors between the swollen and the collapsed states are observed. (c) 2005 Elsevier Inc. All rights reserved.
7th International Conference on Magnetic Resonance in Porous Media (MRPM7), Palaiseau, FRANCE, JUL 04-08, 2004
Keywords: gel; networks; phase transition; relaxometry; Xe-129 spectroscopy

Mechanically tunable curcumin incorporated polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Azad, Lal Busher; Surwase, Sachin S.; Torris, Arun A. T.; Badiger, Manohar V. (Chemistry of Materials, 2016)
We report here on the one-pot synthesis and characterization of curcumin incorporated polyethylene glycol polyurethane (PU-CUR) hydrogels using PEG-4000, 4, 4'-methylenebis (cyclohexyl isocyanate), curcumin in the presence of a cross-linker, 1,2,6 hexanetriol (HT). Besides the physical entrapment, curcumin also provides a partial cross linking in the 3-D structure of the hydrogel. The degree of swelling in hydrogels could be controlled by varying the amount of HT as well as curcumin. The structural characterization of hydrogels was performed using Fourier transform infrared spectroscopy, high-resolution mass spectrometry, UV and fluorescence spectroscopy. The wide-angle X-ray scattering studies revealed the existence of crystalline domains of PEG, and the small-angle X-ray scattering studies showed the presence of lamellar microstructures. Porous structure in the hydrogel was created by cryogenic treatment and lyophilization. Scanning electron microscopy and microcomputed tomography imaging of hydrogels showed the presence of interconnected pores. The mechanical strength of the hydrogels was measured using a universal testing machine. The observed tensile and breaking compression strengths for the equilibrium swollen gels were found to be in the range of 0.22-0.73 MPa and 1.65-4.6 MPa, respectively. Detailed in vitro biological experiments showed the biocompatibility of gels, cytostatic dosage of curcumin, selective toxicity toward cancer cell lines, and antibacterial property. These gels show promising applications as scaffolds and implants in tissue engineering.

Mechanism of the formation of microphase separated water clusters in a water-mediated physical network of perfluoropolyether tetraol - Deshpande, Ashwini A.; Torris, Arun A. T.; Pahari, Swagata; Menon, Shamal K.; Badiger, Manohar V.; Rajamohanan, P. R.; Wadgaonkar, Prakash P.; Roy, Sudip; Tonelli, Claudio (Soft Matter, 2018)
Perfluoropolyether tetraol (PFPE tetraol) possesses a hydrophobic perfluoropolyether chain in the backbone and two hydroxyl groups at each chain terminal, which facilitates the formation of hydrogen bonds with water molecules resulting in the formation an extended physical network. About 3 wt% water was required for the formation of the microphase separated physical network of PFPE tetraol. The mechanism responsible for the microphase separation of water clusters in the physical network was studied using a combination of techniques such as NMR spectroscopy, molecular dynamics (MD) simulations and DSC. MD simulation studies provided evidence for the formation of clusters in the PFPE tetraol physical network and the size of these clusters increased gradually with an increase in the extent of hydration. Both MD simulations and NMR spectroscopy studies revealed that these clusters position themselves away from the hydrophobic backbone or vice versa. The presence of intra-and inter-chain aggregation possibility among hydrophilic groups was evident. DSC results demonstrated the presence of tightly and loosely bound water molecules to the terminal hydroxyl groups of PFPE tetraol through hydrogen bonding. The data from all the three techniques established the formation of a physical network driven by hydrogen bonding between the hydrophilic end groups of PFPE tetraol and water molecules. The flexible nature of the PFPE tetraol backbone and its low solubility parameter favour clustering of water molecules at the terminal groups and result in the formation of a gel.